2016
DOI: 10.12659/msm.898323
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in U937 Cells by Using a Combination of Bortezomib and Low-Intensity Ultrasound

Abstract: BackgroundWe scrutinized the feasibility of apoptosis induction in blood cancer cells by means of low-intensity ultrasound and the proteasome inhibitor bortezomib (Velcade).Material/MethodsHuman leukemic monocyte lymphoma U937 cells were subjected to ultrasound in the presence of bortezomib and the echo contrast agent Sonazoid. Two types of acoustic intensity (0.18 W/cm2 and 0.05 W/cm2) were used for the experiments. Treated U937 cells were analyzed for viability and levels of early and late apoptosis. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The theoretical results also showed that oscillating MNPs may generate ultrasound. Ultrasound is proved to give rise to cell apoptosis or dissolution [86,87]. Cheng et al used rod-shaped MNPs to induce HeLa cell viability decrease by about 2-fold than spherical MNPs with the temperature rise of 1.7 ∘ C after being exposed to an AMF (35 kHz), suggesting that AMF-induced oscillation of MNPs was able to mechanically damage cancer cells in vitro [40].…”
Section: Under High Frequency Magnetic Fieldsmentioning
confidence: 99%
“…The theoretical results also showed that oscillating MNPs may generate ultrasound. Ultrasound is proved to give rise to cell apoptosis or dissolution [86,87]. Cheng et al used rod-shaped MNPs to induce HeLa cell viability decrease by about 2-fold than spherical MNPs with the temperature rise of 1.7 ∘ C after being exposed to an AMF (35 kHz), suggesting that AMF-induced oscillation of MNPs was able to mechanically damage cancer cells in vitro [40].…”
Section: Under High Frequency Magnetic Fieldsmentioning
confidence: 99%